2008
DOI: 10.1007/s10350-008-9325-1
|View full text |Cite
|
Sign up to set email alerts
|

Segmental vs. Extended Colectomy: Measurable Differences in Morbidity, Function, and Quality of Life

Abstract: Measurable compromises in long-term bowel function and quality of life were observed after extended vs. segmental resections. The relative differences in patient-related outcomes should be deliberated against the clinical benefits of extended resection for the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 28 publications
2
91
0
4
Order By: Relevance
“…c-d Intraoperative pictures show the cecum in the right hypochondrium just below the liver, while the hepatic flexure is anastomosed to the rectum The sparing of the right colon, ileocecal valve and terminal ileum has been shown to ensure normal stool consistency and a return of regular transit in contrast to total colectomy. You et al [1] reported a median daily stool frequency of 5 after ileorectal anastomosis, despite considerable dietary restrictions (55.6% of patients) and medication use (19.6% daily). In contrast, in the series by Kontovounisios et al [4], 71.4% of patients had two bowel movements per day following the Deloyers procedure, 21.4% had 3 per day, and 7.2% had 1 per day.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…c-d Intraoperative pictures show the cecum in the right hypochondrium just below the liver, while the hepatic flexure is anastomosed to the rectum The sparing of the right colon, ileocecal valve and terminal ileum has been shown to ensure normal stool consistency and a return of regular transit in contrast to total colectomy. You et al [1] reported a median daily stool frequency of 5 after ileorectal anastomosis, despite considerable dietary restrictions (55.6% of patients) and medication use (19.6% daily). In contrast, in the series by Kontovounisios et al [4], 71.4% of patients had two bowel movements per day following the Deloyers procedure, 21.4% had 3 per day, and 7.2% had 1 per day.…”
Section: Discussionmentioning
confidence: 98%
“…Following extended left colectomy, the residual colon may not reach the rectal stump without undue tension. A total colectomy and ileorectal anastomosis could be an alternative in these cases, although it may be associated with impaired bowel function and reduced quality of life compared to segmental resection [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some guidelines and previous reports have recommended STC, rather than SGC, as the primary treatment for initial CRC in Lynch syndrome patients [3, 4, 10, 11]. On the other hand, previous reports demonstrated that bowel function was significantly worse in patients after STC than after SGC, but general quality of life (QOL) after surgery did not differ significantly between SGC and STC [12, 13]. Obviously, for decision-making regarding surgical strategies, it is important to consider the pros and cons of each surgical procedure, including the risk of metachronous CRC development, bowel function, and QOL after surgery, and life expectancy if differences exist.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patient and provider concerns regarding bowel function and quality of life after more extensive surgery may limit the performance of more extensive surgery even in the presence of abnormal testing. Those undergoing more extensive colonic resection may potentially experience increased stool frequency with a potential impact on quality of life [11]. However, this must be balanced with reduction in CRC risk that is achieved with more extensive surgery.…”
mentioning
confidence: 99%